Antileukemic Activity of Methanol Extract From Stem of Baccaurea macrocarpa, Syzygium jambos, Bouea macrophylla Griff., and Diospyros discolor Willd - Antoni Pardede; Rr Ariessanty Alicia Kusuma Wardhani; Emilda Frasisca (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2020)
A secondary metabolite is a compound produced by plants that are needed for its survival. Those compounds are used as attractant, repellant, and protectant. The three of them, such as color, taste, aroma, and thorns of the plants. These secondary metabolite compounds are important to be revealed. It aims to find new natural resources that are safer, more effective, and efficient in aiding the health sector, such as anticancer, antibacterial, and hepatoprotective and antioxidant properties. The research trends of natural products chemistry sourced from plants that are widely developing are extraction and biological activity, such as anticancer. In this research, the extraction of 1 kg sample was done by using maceration method and produced methanol extract of kapul (Baccaurea macrocarpa) 3.1%, jambu mawar (Syzygium jambos) 2.4%, ramania (Bouea macrophylla Griff) 9% and mentega (Diospyros discolor Willd) 2.7%, and the result of antileukemic activity of methanol extract sample (the survived HL-60 cell percentage) sequentially were 22.6%, 12.7%, 44.1% and 37.3% with the concentration of 100 µg/mL. Jambu mawar (Syzygium jambos) exhibited the highest antileukemic activity with the survived cell percentage (HL-60 cells) of 12.7% among the methanol extract of samples tested.